FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - NELLIYANA, NELLIYANA; AVINA SILMY, SHOFI (E-Jurnal Akuntansi TSM, 2021)
The purpose of study is to obtain an empirical evidence about the influence of variables on firm value. These variables are financial leverage, firm size, return on assets, earnings per share, debt to equity ratio, and net profit margin. The population used in this are non financial companies list on Indonesian Stock Exchange from 2012-2015. There are 156 companies selected as final sample. Data analyzed by using multiple regression method. The result of this research shows that financial leverage, firm size, return on assets, earnings per share, and debt to equity ratio have positive influence on firm value. However, net profit margin have no influence on firm value